Scale-dependent segregation of seeders and resprouters in cork oak (Quercus suber) forests. - Coca, M.; Pausas, J. G. (Oecologia, 2012)
Recent studies showed that disturbances and water availability determine the richness among plants with different post-fire strategies of Mediterranean-type ecosystems. The aim of this study was to determine whether or not the scale of analysis has an influence on the effects of these factors and, therefore, on the segregation of the dominant post-fire strategies, obligate seeders and obligate resprouters, and facultative species. We recorded all woody species and geographical features on 94 (75 m(2)) plots of cork oak woodlands in the southern Iberian Peninsula. For each regenerative type (resprouters, seeders and species with both traits--facultative species), we tested the relationship between the number of species and the predictors using a generalised linear mixed model. The fixed predictor considered at the large scale was altitude, and fixed predictors considered at the local scale were aspect (north/south) and disturbance (fire and clearing by heavy machinery; yes/no). The random predictor was the factor of site. When this factor did not have significant effect for some regenerative types, these relationships was tested using a generalised linear model. Resprouting species were most represented at lower altitudes and in undisturbed sites, while seeders were also at lower altitudes but mostly on south-facing slopes, especially south-facing disturbed sites. For facultative species, site is the most important variable. The proportion of seeders from the total species is not related to altitude, but it is related to disturbance and aspect. These results suggest that there is no segregation of the richness of seeders and resprouters at the large scale (altitudinal gradient). Differences appeared at the local scale (aspect and disturbance).
The following values have no corresponding Zotero field: accession-num: 21863245
Keywords: Cork oak forests; disturbance; Mediterranean vegetation; Moisture regime; Post-fire strategies

Successional trends in standing dead biomass in Mediterranean basin species - Baeza, M. J.; Santana, V. M.; Pausas, J. G.; Vallejo, V. R. (Journal of Vegetation Science, 2011)
Question: Landscape models of fire occurrence in ecosystems assume that the time since the last fire determines vegetation flammability by enabling the accumulation of dead biomass. In this study we ask if Mediterranean basin shrublands respond to these models or, on the contrary, if initial successional stages in these ecosystems could be more flammable than later stages. Location: Mediterranean shrubland in the Valencia region, eastern Spain. Methods: Using different stages of vegetation development (5, 9, 14 and 26 years since the last fire), we first study the structural comiosition of the above-ground biomass in 375 individuals of nine woody species. Then, we measure how the standing dead biomass varies during succession, taking into account the surface cover of each species and the quantity of total dead biomass accumulated in different successional stages (3, 9, 14 and 26 years since the last fire). Results: The largest amount of standing dead biomass at the plant community level is observed in the middle stages of the succession. Early successional species, such as Cistus spp., Ulex parviflorus and Pinus halepensis, have a higher percentage of standing dead biomass at earlier stages in the succession than species typical of later successional stages, e.g. Juniperus oxycedrus, Quercus coccifera and Quercus ilex. Conclusions: The results suggest that monotonic increase in fire hazard with increasing stand age is not necessarily the rule in Mediterranean basin shrublands, since early successional species may accumulate large amounts of standing dead biomass and thus promote fire at early successional stages.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Early and late species; flammability; Retaining dead fuel; Species replacement; Successional stages; woody species

Post-fire tree mortality in mixed forests of central Portugal - Catry, F. X.; Rego, F.; Moreira, F.; Fernandes, P. M.; Pausas, J. G. (Forest Ecology and Management, 2010)
Wildﬁres are a recurrent disturbance in the Mediterranean Basin. However, managers from this region are confronted with a lack of information on the effects of ﬁre on most woody species, which is required for deﬁning sustainable forest management strategies. Following a large wildﬁre in central Portugal (2003), we surveyed the area during the ﬁrst year and assessed the vegetative condition of 1040 burned trees from 11 different species. Among those trees, 755 individuals were selected and monitored annually for 4 years. At the end of the study, almost all the broadleaved trees survived, while most coniferous died. In spite of the low mortality observed in broadleaves, most were top-killed and regenerated only from basal resprouts, which implies a slow recovering process. Quercus suber, however, showed vigorous post-ﬁre crown resprouting and was the most resilient species. We ﬁtted logistic regression models to predict the probability of individual tree mortality and top-kill from ﬁre injury indicators and tree characteristics. Besides the differences between the two main functional groups (coniferous, broadleaved), bole char height and crown volume scorched or consumed were important predictors of tree responses. Additionally, the main factor determining crown mortality on broadleaved species was bark thickness. The selected models performed well when tested with independent data obtained on four other wild- ﬁres. These models have several potential applications and can be useful to managers making pre-ﬁre or post-ﬁre decisions in mixed forest stands in the western Mediterranean Basin.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Fire effects; Mediterranean ecosystems; Modelling; resprouting; Tree survival; Wildﬁres

Mediterranean vegetation dynamics: modelling problems and functional types - Pausas, J. G. (Plant Ecology, 1999)
Gap models have been applied to a wide range of ecosystems, mainly temperate and boreal forests, but rarely have such models been applied to Mediterranean ecosystems. In the present review we address some problems of gap models for predicting the long-term dynamics of Mediterranean ecosystems, and we suggest plant functional types suitable for modelling based on responses to disturbance. Most gap models do not take into account different life forms, interactions with ﬁre (e.g., resprouting and stimulation of the germination), and underground structures. Long term human impact on Mediterranean ecosystems has made a signiﬁcant impact on the current landscapes. That intense land use, involving long-lived slow-growing species, has had long-term consequences. It is not possible to understand Mediterranean vegetation and to validate any model without considering these factors. The lack of data for Mediterranean species may be overcome by taking into account correlations of traits and trade-offs between different functional types. A simple disturbance-based functional group system is discussed.
Keywords: disturbance; Fire ecology; gap models; Mediterranean; resprouting